Political Analysis Of Prabowo Subianto's Branding Through Instagram Social Media @Prabowo: Case Study Of The 2024 Election Campaign - Atala Atala; Muhammad Prakoso Aji (UNIVERSITAS PAKUAN, 2024)
This journal will analyze Prabowo Subianto's political branding strategy during the 2024 election campaign period through Instagram social media. This research review through descriptive qualitative research method explores how the Prabowo Subianto campaign's social media team managed to package interesting content on Instgaram as an effort to form a positive political branding or image for Prabowo Subianto. This research review through descriptive qualitative research method explores how the Prabowo Subianto campaign's social media team managed to package interesting content on Instgaram as an effort to form a positive political branding or image for Prabowo Subianto. The target of the campaign team, especially the social media team, is young voters or Generation Z, which are the first voters in the 2024 elections, so campaign content must be interesting and innovative. The research shows that Prabowo Subianto's success in winning the 2024 election was achieved through digital campaigns on social media, especially Instagram. The use of the term